Cyclic and linear dithienyl-anthryl vinylenes: synthesis, X-ray crystallography, spectroscopic properties, and photoinduced mechanical motions. Issue 11 (28th February 2022) - Wu, Pin-Rong; Wang, Chi-Hsien; Chen, Yi-Wen; Lin, Yen-Jen; Ide, Tomohito; Tsuchido, Yoshitaka; Sei, Yoshihisa; Horie, Masaki
Abstract : We report the synthesis of cyclic and linear dithienyl-anthryl vinylenes, exhibiting photoinduced conformational changes and photomechanical motions in solution and solid states, respectively. Abstract : Cyclic and linear conjugated molecules featuring 9, 10-dithienylanthracene linked with vinylene were synthesized by McMurry coupling, ring-opening metathesis polymerization (ROMP), and dehydration. The cyclic and linear dimers displayed strained ring and planar structures by single-crystal X-ray crystallography, respectively. UV-Vis and photoluminescence (PL) spectra of the cyclic dimer in benzene solution exhibited reversible changes in absorbance and PL intensity by UV irradiation and reversion by heating. The reversion followed the first-order equation, giving a kinetic constant of 0.75 min −1 at 35 °C and an activation energy of 70.9 kJ mol −1 . Computational studies based on density functional theory supported the explanation of the experimental results. These spectral changes were attributed to unique conformational changes, particularly the flipping of the alkylated thienyl group. Furthermore, a single crystal of the cyclic dimer showed photoinduced bending. Contrarily, a free-standing film of polyvinylene synthesized via ROMP and polyimine synthesized via dehydration exhibited photoinduced elongation and bending, respectively.